THE EFFECT OF BAND ENGINEERING OF SEMICONDUCTORS AND OTHER FACTORS ON PHOTOCATALYIC DEGRADATION OF ORGANIC POLUTANTS, TOWARDS A SCALE OF PHOTOCATALYTIC EFFECTIVENESS: A MULTIFACTORIAL EQUATION FOR THE PHOTOCATALYIC EFFICENCE. A REVIEW - Maria Luisa Valenzuela Valdes; Carlos Díaz; Marjorie Segovia (Journal of the Chilean Chemical Society, 2025)
The direct conversion of solar energy using a photocatalyst in a degradation of a pollutant reaction is a source of a sustainable and clean environment remediation. In general, photocatalyst are semiconductors that possess valence and conduction bands. These energy bands permit the absorption of photon energy to excite electrons in the outer orbitals of the photocatalyst. Photoexcited electron and hole pairs can subsequently induce a reaction that degrade organic pollutant molecules. Photocatalyst degradation of pollutants is affected by the band level and crystallinity of the photocatalyst among others, therefore, band engineering using chemical modifications as particle size, morphology and physical as band gap could create photocatalyst suitable for the large-scale photodegradation of organic pollutant. In this Review, different factors of the photocatalyst obtained by solid-state, such as size, morphology, band gap and others are analyzed in the photocatalyst efficiency of the degradation of organic contaminant. This review involves binary metal oxide photocatalyst of the MxOy type, prepared from a solid-state route. The photocatalytic degradation of blue methylene using our  the solid-state TiO2, Fe2O3, NiO, ReO3, IrO2, Rh2O3, Rh/RhO2, and the actinide ThO2 prepared nanostructured metal oxides by a solid state method  is described and discussed. Also, other studies of photocatalysis also prepared in solid state for the degradation of methylene blue and reported in the literature are shown and analyzed.  With regard the photocatalytic efficiency, factors such as the particle size and morphology, the crystalline phase and the pyrolysis temperature used in the solid-state preparation method are very important. A multifactorial equation that summarizes the main factors that govern the photocatalytic efficiency of a photocatalyst is proposed. A parameterization of these factors is discussed through an equation of the photocatalytic efficiency as a function of these parameters. The importance of each of these parameters/factors in the photocatalytic efficiency against methylene blue degradation is discussed.